Chaco low-level jet events characterization during the austral summer season - Salio, Paola Veronica (2002)
Previous studies showed a relationship between convection maxima and the convergence of vapor flux over southeastern South America. Nicolini and Saulo [2000] explored the hypothesis of an intensification of this mutual dependency during the Chaco Jet events. They defined these events as extreme cases of low-level jets east of the Andes that penetrate southernmost to 25°S using ETA operative products during the 1997-1998 austral warm season. The interest of the present paper centers on the climatic characterization of the Chaco Jet events (CJEs) and the possibility of researching this hypothesis using the European Centre for Medium-Range Weather Forecasts reanalyses (ERA), which cover a 15-year period (1979-1993). The CJEs represent a subensemble of low-level jet events east of the Andes that are infrequent in the ERA data set. Their duration varies from 1 to 10 days, more frequently extending from 1 to 5 days. The outstanding features of the circulation and the thermodynamic field that represent this ensemble are a maximum contrast of air masses in a latitude close to 39°S, the presence of a trough centered on 70°W within a baroclinic wave train penetrating from the Pacific Ocean, and a maximum of heat and moisture over northen Argentina and Paraguay. During the CJEs, there is an important flux of moisture and convergence at low and mid levels that is about 10 times more intense than the summer mean. The intensity found in the water vapor flux anomaly reinforces the importance, of studying these episodes for the purpose of determining the water balance over southeastern South America. The statement that the CJEs represent an important characteristic of the southeastern South American climate is founded on the fact that, although the CJEs only represent 17% of the austral summer days, they account for a significant fraction of the precipitation (a maximun of 55%) over northeastern Argentina. However, it is indispensable to contrast these results with future field experiments to test the hypothesis addressed in this paper. Copyright 2002 by the American Geophysical Union.